Mathematical representation ability and confident character assisted by Schoology with the NHT method and thematic approach - Sabrina, Atika Nur; Hidayah, Isti; Kharis, Muhammad (Unnes Journal of Mathematics Education, 2021)
This study aims to determine the students’ mathematical representation ability and confidence character assisted by Schoology with the Numbered Heads Together (NHT) method and thematic approach and describe the mathematical representation ability based on the character of self-confidence. The subjects of this study were students of class VIIF and VIIH, one of Junior High School in Semarang. The method used is a mixed method. The results of the study show that: (1) The students’ mathematical representations ability and confident character assisted by Schoology with the NHT method and thematic approaches are better than learning without Schoology; (2) the mathematical representation ability based on the character of self-confidence is (a) students with high self-confidence implement indicators visual and symbolic representations; (b) students with medium self-confidence implement indicator symbolic representation; and (c) students with low self-confidence not implementing of indicators visual, symbolic, and verbal representation abilities.